2018
DOI: 10.1371/journal.pone.0198719
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure factors for mental and behavioral disorders at work: The FOREC thesaurus

Abstract: BackgroundMental disorders in the workplace are a major public health problem. Knowledge of the impact of the psychosocial work environment on mental and behavioral disorders can assist occupational physicians in the identification and description of occupational risk situations, and help to define priority actions. However, no classification for occupational exposure factors is currently available. We aimed to build a thesaurus of “Organizational, Relational, Ethical and other Contributing Factors” (FOREC) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…The occupation of participants also statistically predicted depression and stress. This finding is consistent with previous literature [50][51][52][53] and could be due to the challenges such as low motivation, marginalization, low self-esteem, physical/emotional exhaustion emanating from a heavy workload, and long working periods experienced by people at their workplaces, as these are known risk factors of mental health problems [54].…”
Section: Discussionsupporting
confidence: 92%
“…The occupation of participants also statistically predicted depression and stress. This finding is consistent with previous literature [50][51][52][53] and could be due to the challenges such as low motivation, marginalization, low self-esteem, physical/emotional exhaustion emanating from a heavy workload, and long working periods experienced by people at their workplaces, as these are known risk factors of mental health problems [54].…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports from frontline medical staff during the COVID-19 pandemic highlighted the risk of poor mental health following extended exposure to traumatic experiences ( Gold, 2020 ; Robertson et al, 2020 ; Zhang et al, 2020 ). In contrast to high-risk occupations, in general settings, work characteristics (such as decision latitude and effort-reward imbalance) appear to be more closely associated with mental disorders than occupational category ( Stansfeld and Candy, 2006 ; Stansfeld et al, 2013 ; Chamoux et al, 2018 ). Broader socio-political contexts also matter, in that non-work experiences also impact on workers.…”
Section: Introductionmentioning
confidence: 73%
“…[38][39][40] Other reports have recommended regular follow-ups from occupational health staff for workers at risk for mental health problems. 41,42 In Japan, the guidelines on mental health issued by the Ministry of Health, Labour, and Welfare stipulate that the roles of occupational physicians and occupational health nurses include responding to consultations with workers and reducing worker stress by improving the working environment. 24 Indeed, an intervention study of cognitive-behavioral therapy training conducted in collaboration with cognitive-behavioral therapy specialists and occupational health staff in Japan reported reduced feelings of depression in workers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the role of occupational physicians in helping employees with mental health issues return to work 38–40 . Other reports have recommended regular follow-ups from occupational health staff for workers at risk for mental health problems 41,42 . In Japan, the guidelines on mental health issued by the Ministry of Health, Labour, and Welfare stipulate that the roles of occupational physicians and occupational health nurses include responding to consultations with workers and reducing worker stress by improving the working environment 24 .…”
Section: Discussionmentioning
confidence: 99%